Empowering the UMKM Economy, BUMK and Halal Tourism to Improve the Economy in Pengidam - Kurlillah, Anis; Rizki, Maulana; Lina, Siti Rosa; Muzakir; Nita; Safwandi (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2023)
This community service activity aims to overcome the economic problems that occur in Pengidam Village so that the utilization of village funds or other sources can be more optimally focused on the village's economic potential. The problem that occurs in Pengidam Village is the lack of public awareness in improving the economy from supporting sectors including: BUMK (Village-Owned Enterprises), UMKM (Micro, Small and Medium Enterprises) and Tourism. This sector is a fulcrum in developing the village economy so that it is more advanced and becomes a pilot village in the region, especially in Aceh Tamiang District, Aceh Province. Increasing knowledge and digitalization is one of the indicators in economic development both in terms of legality, packaging and marketing of a product from the UMKM sector. Keywords: UMKM, BUMK, and Halal Tourism